2018
DOI: 10.29252/mlj.12.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CCR5Δ32 Polymorphism in Patients with Systemic Lupus Erythematosus and Healthy Individuals

Abstract: Background and Objectives: CC chemokine receptor type 5 (CCR5) is a chemokine receptor expressed at high levels on the surface of T-cells. A 32-bp deletion in the coding region of the CCR5 (CCR5Δ32) leads to production of an incomplete protein that is not expressed on the cell surface. CCR5Δ32 may be involved in development of autoimmune disease, such as systemic lupus erythematosus. We investigated frequency of the CCR5Δ32 polymorphism in SLE patients and healthy controls, and evaluated the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This would suggest the role of biogeographic background in the association of the rs333 variability and the susceptibility to SLE. On the other hand, the lack of association was also reported in patients from Poland [ 43 ], Iran [ 44 ] the Netherlands [ 45 ] and Spain [ 46 ]; the observation being consistent with that made in this study. Conversely, the association was revealed in a mixed cohort of patients from Ohio, Colombia and San Antonio (Texas) [ 26 ] as well as in a female sample from Brazil [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would suggest the role of biogeographic background in the association of the rs333 variability and the susceptibility to SLE. On the other hand, the lack of association was also reported in patients from Poland [ 43 ], Iran [ 44 ] the Netherlands [ 45 ] and Spain [ 46 ]; the observation being consistent with that made in this study. Conversely, the association was revealed in a mixed cohort of patients from Ohio, Colombia and San Antonio (Texas) [ 26 ] as well as in a female sample from Brazil [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, in the study of Heydarifard et al . [ 44 ] no significant association between the rs333 status and clinical features of SLE was revealed. In this study, no statistically significant associations between the symptoms (or lack thereof) in patients with SLE and/or DLE were found with any allele or genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the CCR5D32 variant did not vary significantly between groups The frequency of the CCR5D32 variant was significantly higher in healthy euro-Brazilian controls (0.075) than in euro-Brazilian SLE patients (0.027) (p=0.002); Patients carrying the CCR5D32 variant were predisposed to the development of class IV nephritis (p=7E-6) Schauren et al (185) (Continued) erythematosus and severity in clinical outcomes (96). Studies performed in different populations have found no association between the variant and the development of systemic lupus erythematosus (205)(206)(207)(208). Such divergence involving the results mentioned above deserves attention and, therefore, more studies in other populations are required.…”
Section: Ar Patients 83 Healthy Individualsmentioning
confidence: 99%